ATTITUDES AND BELIEFS OF PATIENTS OF NON-CODIFIED TRADITIONAL MEDICINE IN BELAGAVI REGION - Bhat, Shripad; Naik, Ashok C.; Kholkute, Sanjiva D. (International Journal of Research -GRANTHAALAYAH, 2018)
Traditional Medicine (TM) medicine is a health care system that has ancient roots, faith of the rural community and cultural background. The study was conducted to out the attitudes and beliefs of patients visiting traditional healers. Ten traditional healers in rural area of Belagavi district representing different categories of non-codified traditional healing practices were included in the study. The data was collected on patients who were willing and agreed to answer the questionnaire. Forty questionnaires were tested and the preliminary results were assessed for validity. The questionnaire data was entered in Microsoft Excel and analysis was carried out using Statistical Package for Social Sciences (SPSS) version16.0 software. The results are based on the descriptive data of 322 patients. Most of the participants were younger than 40 years old (62.1%). 201 (62.4%) patients visited traditional practitioner minimum 2 times in their life time. Among them, 94.5% of patients reported satisfaction with TM. 263 (81.7%) patients had previous history of treatment from other systems of medicine for the same health problems before visiting traditional healers. Among them 191 (72.6%) patients were dissatisfied with previous treatment, out of which 181 (94.8%) had taken modern medicine. The majority 256 (79.5%) patients visited because of their positive attitudes and beliefs towards traditional medicine. The study indicates that people do visits traditional healers and have a faith in traditional healers and their medicine.